Akuntabilitas Pengelolaan Dana BOS Di SDN Pringgowirawan 02 Kecamatan Sumberbaru Kabupaten Jember Tahun 2014 - Tutus Julantika; Djoko Supatmoko; Taufik Kurrohman (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
his research aims to know the application of accountability system within the management of Accountability Of School Operational Assistance (BOS) fund and how the responsibility of Accountability Of School Operational Assistance (BOS) fund is used foward Pringgowirawan 02 Elementary school Sumberbaru in 2014 method of collecting data in the research is done through interview with the school principal and the chamberlain of Accountability Of School Operational Assistance (BOS). Besides, the researcher also uses direct observation foward the school area. The goal of this research is the management of Accountability Of School Operational Assistance (BOS) fund which is gained from the total planned and the total used of Accountability of School Operational Assistance (BOS) fund itself. The compatibility of Accountability of School Operational Assistance (BOS) fund used can be seen from the ratio shown. Ratio in this research is the number which is demonstrated the ability of school to use Accountability of School Operational Assistance (BOS) fund based on the planned Accountability of School Operational Assistance (BOS) fund in the earlier semester.